A MEASUREMENT OF RURAL TOURISM DESTINATIONS’ COMPETITIVENESS - Ioana Maria DUMITRU (m. TRIPON); Smaranda Adina COSMA (Studia Universitatis Babeş-Bolyai Negotia, 2023)
The trend of rural tourism is growing and is becoming increasingly significant for most nations. Rural tourism is believed to have the potential to revive traditional approaches and perspectives on tourism and provide new dimensions to sustainable growth. Romania is regarded as one of the main destinations with a high potential in sustainable tourism development, due to its beautiful, unspoiled rural landscapes, traditions, and rustic lifestyle. Tourism, as a development tool, in rural communities, is one of the major concerns. The scarcity of case studies on rural tourist competitiveness, particularly in Romania, is what inspired the current research. This study attempts to investigate the factors that impact Romania’s rural tourism’s competitiveness and develop a conceptual framework for measuring it. In conducting our research, there were employed both exploratory and descriptive approaches. Secondary data from statistical and published research and studies were gathered, and it were collected primary data through surveys and personal interviews. The objective of the current research was to introduce a distinct and exclusive method of evaluating tourism in rather small regions with unique characteristics and applied and test the proposed model to Maramures region. The paper concludes that measuring and understanding rural tourism competitiveness and dynamics is essential for supporting sustainable development in rural areas, and it is of great importance for practitioners, policy makers and researchers.